The Future of Aid 2 : The Big Push - Harford, Tim; Klien, Michael (World Bank, Washington, DC, 2012)
This note considers the future of aid from the perspective of the 2005-2030 time frame. It offers a possible scenario for the future, with responses of the aid industry to falling numbers of people in absolute poverty and to the growing ability of poor countries to borrow from the market. A companion note (report 32124) offers a second scenario. The notes were written in the spirit of plausible stories about the future to encourage thinking about possible responses.